Miniaturized lumped quadrature hybrid using inductance‐ and integration‐enhanced inductors for VHF band applications. Issue 12 (23rd September 2022) - Song, Zichen; Zhou, Bo
Abstract: A miniaturized lumped‐element quadrature hybrid is proposed for the very high frequency (VHF) band applications. The overall size reduction of the hybrid is achieved by the proposed three‐dimensional (3D) inductance‐ and integration‐enhanced inductors (IIEIs), which etch planar internal turns inside the conventional spiral inductor for inductance increment and size reduction. The hybrid is implemented on a 10‐layer low‐temperature co‐fired ceramic (LTCC) substrate with a size of only 0.0048 × 0.0027 × 0.0004 λg 3 . Measured S 11, S 21, S 31 and S 41 are better than −18, −5, −3.6, and −13 dB from 45 to 55 MHz, respectively. And the measured amplitude imbalance and phase difference between the through and coupled port are within 1.4 dB and 90° ± 1°, respectively. The proposed hybrid has wide applications in super heterodyne intermediate frequency (IF) circuit, Tesla magnetic resonance imaging (MRI) equipment and maritime communications.